2019
DOI: 10.1007/s12144-019-00194-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutual mate choice drives the desirability of altruism in relationships

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Whilst there are a number of established adaptive explanations as to why we help others at a cost to ourselves (Alexander 1987;Buss 2004;Hamilton 1964;Maynard Smith 1964;Trivers 1971), these theories tend to focus on helping kin or involve reciprocation. More recently, the literature has suggested that, in some part, altruism may also be driven through sexual selection, specifically through female mate choice (Bhogal et al 2016;Farrelly and King 2019;Iredale et al 2008;Van Vugt and Iredale 2013). For example, we see sexual differences in the way in which altruism is expressed.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whilst there are a number of established adaptive explanations as to why we help others at a cost to ourselves (Alexander 1987;Buss 2004;Hamilton 1964;Maynard Smith 1964;Trivers 1971), these theories tend to focus on helping kin or involve reciprocation. More recently, the literature has suggested that, in some part, altruism may also be driven through sexual selection, specifically through female mate choice (Bhogal et al 2016;Farrelly and King 2019;Iredale et al 2008;Van Vugt and Iredale 2013). For example, we see sexual differences in the way in which altruism is expressed.…”
Section: Introductionmentioning
confidence: 89%
“…However, the answer is not always so clear cut. In a recent study by Farrelly and King (2019), when men and women viewed images of the opposite sex accompanied by different altruistic scenarios, both men and women rated those who were described as altruistic as more desirable as a mate.…”
Section: Is Altruism a Signal That Is Attractive To The Opposite Sex?mentioning
confidence: 98%
“…The typical instrument used to explore gender differences in altruistic behaviour is the Dictator Game (DG), where dictators' donations are taken as a measure of the individual's general altruistic tendencies (Brañas-Garza, 2006, 2007Brañas-Garza et al, 2018;Charness & Gneezy, 2008;Croson & Gneezy, 2009;Farrelly et al, 2016;Farrelly & King, 2019). Recently qualitative interviews were introduced to collect occupational values, gender stereotypes and altruism: surveys and web-surveys estimated valuebased goals that are mainly accepted at different levels.…”
Section: The Main Methods Used Within the Research Fieldmentioning
confidence: 99%
“…Some lines of research have considered the social representation of altruism in relation to gender: many studies in psychology and economics aim to explore differences in altruism's gender beliefs and their effects upon behaviour (Boschini et al, 2018;Salgado, 2018;Croson & Gneezy, 2009). Others focus on the role that altruism plays in the choice of partners, above all in women's preferences and in long-term relationships (Farrelly & King, 2019;Farrelly et al, 2016;Kelly & Dunbar, 2001). In these studies, simple economic games, such as the Dictator Game, were used to examine the impact of gender on altruistic behaviour.…”
Section: Introduction 11 Altruismmentioning
confidence: 99%
“…This could be due to the fact that the most research finds that women are attracted to men who display benefit-provisioning behavior (see Bhogal, Farrelly, Galbraith, Manktelow, & Bradley, 2020; Bhogal et al, 2019; Farrelly, Lazarus, & Roberts, 2007; Phillips, Barnard, Ferguson, & Reader, 2008). However, there is some (although limited) research showing that men are attracted to women who display benefit-provisioning behavior (although this effect is generally more prominent in women than men; see Bhogal, Bartlett, & Farrelly, 2019; Farrelly & King, 2019). However, because of the majority of research showing the importance of heroism in female mate choice, we expected women to find heroism more desirable than men.…”
mentioning
confidence: 99%